Pawongan Sebagai Konsep Multikultur Dalam Ajaran Agama Hindu Di Bali - Ketut Bali Sastrawan; I Made Ariasa Giri (Purwadita : Jurnal Agama dan Budaya, 2023)
The Hindu community in Bali has a very high sesnse of tolerance. The teching of Hinduism have never discriminated against human, be it in terms of etchnicity, religion, race or culture. Hinduism teaches human to be able to live in harmony with fellow human beings. Maintaining harmonious humah relations or ini Bali it is called pawongan, manifested by public awareness which has indirectly manifested multicultural values in society. The embodiment of these multicultural values includes: democracy, pluralism and humanism